Tax Awareness, Tax Services Quality, and Tax Sanctions on Individual Taxpayer Compliance - Cheka Rahiem; Kenny Ardillah Ardillah (The Accounting Journal of Binaniaga, 2022)
The research aims to know the effect of tax awareness, tax services quality, and tax sanctions on individual taxpayer compliance. The population in this research is individual taxpayers in the tax office of Pratama Jakarta Sunter, with a total of 118.611 taxpayers. The research sample is determined by the slovin method and becomes as many as 100 respondents from 132 employees of MSME's business owners. Primary data from the questionnaire was obtained in 2021 during the Covid-19 pandemic. The data analysis method used in this research is the accidental sampling method. The technique to determine the sample is using random sampling. The result has shown that tax awareness, tax services quality, and tax sanctions positively and significantly affect individual taxpayer compliance.